The Sustainable Development Agenda Needs to Include Long-term Care - Pot, A.; Briggs, Andrew; Beard, J. (Elsevier, 2018)
The rapid ageing of populations around the world and the associated shift in the burden of disease from infectious to chronic conditions are creating complex challenges for national governments. Addressing the needs of these older populations in a sustainable and equitable way, will be a fundamental pillar of socioeconomic development in the 21st Century. The World Health Organization (WHO) Global strategy and action plan on ageing and health, which was adopted by all the Organization's 194 Member states in 2016, provides a clear framework for global action. One critical priority is to establish sustainable and equitable long-term care systems in every country. WHO defines long-term care as “the activities undertaken by others to ensure that people with, or at risk of, a significant ongoing loss of intrinsic capacity can maintain a level of functional ability consistent with their basic rights, fundamental freedoms and human dignity”. These activities include both social care and health care, as well as contributions from other sectors, such as education or transport. And these activities need to be effectively coordinated if they are to efficiently, equitably and sustainably meet the needs of older people. This requires the stewardship of governments to ensure that: care is accessible and affordable; the rights of older people to lives of meaning and dignity are upheld regardless of their physical or mental capacity; services are oriented around the individual's specific needs; caregivers are supported; the workforce (both paid and unpaid) are treated fairly; and older people's intrinsic capacity is maintained for as long as possible. WHO has proposed three inter-related strategies to establish and sustain long-term care systems. System infrastructure needs to be developed and continually improved. The capacity of the workforce needs to be strengthened and families and communities must be supported. And the care and support provided needs to be more person-centred and integrated, underpinned by minimum standards and accreditation for care providers. This paper outlines some of the critical issues confronting governments in countries at all levels of development if this ambitious vision is to be achieved.